Writing and Conceptual Learning in Science: An Analysis of Assignments. (January 2019) - Gere, Anne Ruggles; Limlamai, Naitnaphit; Wilson, Emily; MacDougall Saylor, Kate; Pugh, Raymond
This systematic review of 46 published articles investigates the constructs employed and the meanings assigned to writing in writing-to-learn assignments given to students in science courses. Using components of assignments associated with the greatest learning gains—meaning making, clear expectations, interactive writing processes, and metacognition—this review illuminates the constructs of writing that yield conceptual learning in science. In so doing, this article also provides a framework that can be used to evaluate writing-to-learn assignments in science, and it documents a new era in research on writing to learn in science by showing the increased rigor that has characterized studies in this field during the past decade.